ANALYSIS OF PREVENTIVE MAINTENANCE KOMATSU HD 785-7 AT PT XYZ (Universitas Pendidikan Indonesia, 2025)
This study aims to analyze the maintenance of the Komatsu HD 785-7 unit at PT XYZ, a contracting company engaged in coal mining in Indonesia. The research method used is qualitative, which includes literature study and field surveys. The literature study was conducted by examining the rules and standard operating procedures at XYZ, as well as the specifications of the Komatsu HD 785-7 unit through the manual book and related journals. The field survey was carried out to collect data on unit specifications, maintenance schedules, and operational costs through interviews and observations. The results of the study indicate that the availability of components according to the type of maintenance is crucial to support the smooth maintenance process. The conclusion of this study emphasizes the need for a systematic and planned maintenance approach to maximize the performance of heavy equipment and reduce operational costs. This research is expected to serve as a reference for other companies in effectively managing heavy equipment maintenance.